Quality of life and oral health: understand this relationship. - Coelho Paraguassu, Eber; Celis de Cardenas, Anneli Mercedes (Brazilian Journal of Implantology and Health Sciences, 2023)
When we think of quality of life, we rarely associate this concept with oral health. However, valuing a preventive conduct with regard to this aspect can have consequences ranging from maintaining the individual's well-being to even improving their self-esteem and social relationships. Thinking about it, we separate some of the main factors that show the close relationship between quality of life and oral health. Check it out below and find out how fundamental mouth care can be! Prevention of diseases Periodic visits to the dentist and proper oral hygiene on a daily basis are extremely important factors. In addition to aesthetic factors, it is worth mentioning that several diseases can manifest in the mouth or even be aggravated by poor oral health. One of these diseases is diabetes mellitus, which can bring great discomfort to patients who have gingivitis or periodontitis. According to studies, it may occur due to the difficulty that individuals with diabetes have in fighting bacterial infections. Good hygiene, as well as periodic visits to the dentist, can also prevent gingivitis and periodontitis, which cause great discomfort. Therefore, it is worth investing in this care that should be daily! Improvement of social relationships Oral health can have extremely relevant consequences for an individual's social relationships. A poorly cleaned mouth, with missing teeth or some type of aesthetic alteration can cause a bad external impression to an individual who does not have this type of concern. In this way, the lack of cleanliness and care for the health of the mouth can have impacts from social work relationships, even in love relationships, which are situations where the aesthetic aspect of the individual is relevant. Improved self-esteem A well-groomed mouth can make all the difference in maintaining good self-esteem. It composes an important aesthetic function in the face, which means that its due integrity is of enormous importance, both in the individual's appearance and in his self-acceptance. The loss of teeth, for example, can have serious consequences for people's self-esteem, at any age. A smile is part of the expression of several positive emotions, and drastic changes such as the loss of teeth can significantly undermine the impetus to express them. Consequently, there will be a progressive loss in the self-esteem of the person with this type of problem. Another change caused by lack of care for oral health can be bad breath, which is a condition that can be caused by poor oral hygiene or even the lack of it. From bacterial decomposition in the mouth, extremely unpleasant odors are released, which can be a source of embarrassment for people who have this type of problem. Oral health in childhood Even in the period of milk teeth, it is very important that there is special care for oral health in childhood. Frequent cleaning prevents the proliferation of bacteria that cause cavities, which can cause more serious problems after the birth of permanent teeth. It is also worth noting that, in some cases, orthodontic correction of teeth can be performed more quickly in childhood. This occurs because the skull has not yet fully grown and the consequent calcification of the bones, which allows for greater mechanical movement of the teeth in cases where there is a need for correction. Oral health in old age Care for the health of the mouth can be extremely important in old age. At this stage, it is common for there to be a natural weakening of different parts of the body, which also includes the teeth. Thus, negligence towards oral health can have consequences for the self-esteem of the elderly. It is also common for the elderly to have diseases such as diabetes, which requires more intense care in the prevention of gingivitis and periodontitis. From proper attention to oral health, it is possible to considerably increase the quality of life of the elderly.